Pluralisme Hukum Waris di Palampang: Studi komprasi Hukum Islam dan Hukum Adat dalam Praktik Pewarisan: Analysis of Islamic Law and Customary Law in Inheritance Practices - Syuaib, Nurul Aqarrah; Ansar, Lukman (Universitas Islam Negeri Alauddin Makassar, 2025)
This study discusses the dynamics of legal pluralism in the practice of inheritance distribution in Palampang Village, Bulukumba Regency, which shows the complex interaction between Islamic inheritance law and the customary inheritance law of the Bugis people. The main issue raised is how the community navigates two different legal systems in inheritance practices, particularly in the context of applying the 2:1 provision between male and female heirs according to Islamic law. The discussion covers the extent to which Islamic law provisions are implemented textually, as well as how cultural values such as family deliberation, social contribution, and empathy are passed down and influence customary mechanisms in inheritance distribution. This study uses a descriptive qualitative approach with data collection methods in the form of in-depth interviews with traditional leaders, religious leaders, and heirs, as well as field observations of inheritance practices. The results of the study show that the Palampang community applies a pluralistic legal system with a greater tendency toward local customs in inheritance practices. The 2:1 distribution provision in Islamic law is rarely strictly implemented because it is considered to not fully reflect social realities and the actual contributions of each heir. An important finding from this study is that legal pluralism does not create conflict if it is managed through family deliberation mechanisms and social approaches based on local values. The academic recommendation from this study is the need for a model of integration between Islamic law and customary law that respects the cultural values of the local community without neglecting the principles of justice in Sharia, as well as strengthening the capacity of community leaders in facilitating pluralistic law-based inheritance settlements.